2017
DOI: 10.1007/s00284-017-1286-y
|View full text |Cite
|
Sign up to set email alerts
|

Abilities of Co-cultures of Brown-Rot Fungus Fomitopsis pinicola and Bacillus subtilis on Biodegradation of DDT

Abstract: DDT (1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane) is one of the pesticides that are hazardous for the environment and human health. Effective environmental-friendly treatment using co-cultures of fungi and bacteria is needed. In this study, the bacteria Bacillus subtilis at various volumes of 1, 3, 5, 7, and 10 mL (1 mL ≈ 6.7 × 10 CFU) were mixed into 10 mL of the brown-rot fungus Fomitopsis pinicola culture for degrading DDT during a 7-days incubation period. DDT was degraded by approximately 42% by F. pini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 46 publications
0
30
0
1
Order By: Relevance
“…The synergistic co-cultures P. aeruginosa -P. ostreatus [17], P. brevispora -B. subtilis [19], G. lingzhi -B. subtilis [21] were previously reported as having degradation efficiency of 75~86%. In the cases of brown-rot fungus, Sariwati et al [43] and Sariwati and Purnomo [44] reported that the addition of B. subtilis and P. aeruginosa increased DDT degradation by Fomitopsis pinicola, respectively. Recently, Setyo et al [35] stated that the addition of R. pickettii to D. dickinsii culture enhanced the degradation of DDT from 54~69%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The synergistic co-cultures P. aeruginosa -P. ostreatus [17], P. brevispora -B. subtilis [19], G. lingzhi -B. subtilis [21] were previously reported as having degradation efficiency of 75~86%. In the cases of brown-rot fungus, Sariwati et al [43] and Sariwati and Purnomo [44] reported that the addition of B. subtilis and P. aeruginosa increased DDT degradation by Fomitopsis pinicola, respectively. Recently, Setyo et al [35] stated that the addition of R. pickettii to D. dickinsii culture enhanced the degradation of DDT from 54~69%.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of biosurfactant resulting from R. pickettii and P. eryngii co-culture might produce some toxic metabolites for survival rather than for degrading DDT. To determine the effectiveness of various co-cultures, the ratio optimization (RO) was obtained by comparing the degradation of DDT in co-cultures and the total of that by particular fungi and bacteria [43,44]. RO ≥ 1 indicated the synergistic mechanism between P. eryngii and R. pickettii to degrade DDT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, B. subtilis can be mixed with some brown-rot fungi (BRF), such as Gloephyllum trabeum, Daedalea dickinsii, and Fomitopsis pinicola as well as white-rot fungi (WRF) such as Pleurotus ostreatus, Pleurotus eryngii, and Ganoderma lingzhi. Mixed culture B. subtilis and BRF had been reported to enhance DDT degradation as well as dyes decolorization [29][30][31][32].…”
Section: Analysis Of Degradation Products (Gc-ms)mentioning
confidence: 99%
“…Soil (Chauhan and Singh, 2015;Neerja et al, 2016;Pathak, Chauhan, Ewida and Stothard, 2016) Enterobacter cloacae. Soil (Neerja et al, 2016) Alcaligeneseutrophussp Soil (Erdem and Cutright, 2016) Bacillus species Soil (Sariwati, Purnomo and Kamei, 2017) Lindane Staphylococcus sp Soil (D. Kumar, Kumar and Sharma, 2016) Kocuriasp Soil (D. Kumar et al, 2016) Chromohalobacter sp. Soil (Bajaj, Sagar, Khare and Singh, 2017) Bacillus sp.…”
Section: Fungi Involvement In Biodegradation Of Pesticidesmentioning
confidence: 99%